Yusoff Rono : wira Bukit Kepong - Muhammad Zaidee Daut,, 1974- (Batu Berendam, Melaka :: Institut Kajian Sejarah dan Patriotisme Malaysia, 2008)
Biography of Yusoff Rono, a Malaysian police officer and survivors of Bukit Kepong incident between the police and Malayan Communists during pre-independence Malaya on February 23, 1950.
Includes bibliographical references (p. 107-114).
In Malay.